Prevalence and Trends in Gestational Diabetes Mellitus Among Women in the United States, 2006–2017: A Population-Based Study - Zhou, Tao; Du, Shan; Sun, Dianjianyi; Li, Xiang; Heianza, Yoriko; Hu, Gang; Sun, Litao; Pei, Xiaofang; Shang, Xiaoyun; Qi, Lu (Frontiers in Endocrinology, 2022)
The prevalence of Gestational diabetes mellitus (GDM) increased with the increasing rate of obesity. However, national data on the prevalence and secular trends of GDM during the past 10 years in the United States is lacking. The current study included 37 357 women aged more than 18 years and had ever been pregnant from the National Health Interview Survey (NHIS). We examined GDM prevalence in 2006, 2016, and 2017, with age-standardized to the U.S population in the year 2000. We found that the prevalence of GDM per 100 persons increased from 4.6 (95% CI, 4.1-5.1) in 2006 to 8.2 (95% CI, 7.5-8.9) in 2016 (test for difference; P<0.001), with a relatively increased rate of 78%. Non-Hispanic white women tended to have less increase (2.8%) than Non-Hispanic black women (3.8%), Hispanic women (4.1%), and women with other race/ethnicity (8.4%). The prevalence of GDM in Non-Hispanic white women was higher than that in Non-Hispanic black women in 2006 (4.8% vs 3.5%, P=0.006), such difference became not significant in 2016 (P=0.72). In addition, the increase of GDM from 2006 to 2016 tended to be more evident among women who were overweight (25≤BMI≤30 kg/m2), physically inactive, and with family income below the poverty threshold than women in other BMI ranges, with more physical activity, and with higher incomes. The prevalence of GDM per 100 persons in 2017 was 8.4 (7.6-9.2), and there was no significant change in the overall and subgroups prevalence compared with 2016. Collectively, In the United States, the prevalence of GDM continuously increased, nearly doubled, from 2006 to 2016, and then leveled off in 2017. The increase appeared to be more marked among the minority populations and subpopulations with overweight, insufficient activity, and family income below the poverty threshold.